Design And Implementation Of Oranges Sorting System - Muhamad Taufiq Tamam; Arif Johar Taufiq; Wakhyu Dwiono (Techno (Jurnal Fakultas Teknik, Universitas Muhammadiyah Purwokerto), 2018)
One application of electronics technology in the field of agriculture is to process the yield of citrus fruits, to choose oranges based on size / dimension. If using manpower (manual) requires high accuracy and takes a long time. By using electronics technology it can be eliminated. The aim of this research is to make prototype of sorting tool that can choose orange fruit based on dimension / size. By using laser sensor and photo diode (photo diode) function to know dimension / size of citrus fruit, citrus fruit will be separated according to dimension / size, big or small. Test results show that this tool can work well in accordance with the planned